Oceanic, Latitudinal, and Sex-Specific Variation in Demography of a Tropical Deepwater Snapper across the Indo-Pacific Region - Williams, Ashley J.; Wakefield, Corey B.; Newman, Stephen J.; Vourey, Elodie; Abascal, Francisco J.; Halafihi, Tuikolongahau; Kaltavara, Jeremie; Nicol, Simon J. (Frontiers in Marine Science, 2017)
Deepwater tropical fisheries provide an important source of income and protein to Pacific and Indian Ocean coastal communities who are highly dependent on fish for food security. The development of quantitative assessments and management strategies for these deepwater fisheries has been hindered by insufficient biological and fisheries data. We examine the age-specific demography of the pygmy ruby snapper Etelis carbunculus, an important target species in tropical deepwater fisheries, across 90° of longitude and 20° of latitude in the Pacific and Indian Oceans. Our results show that growth of E. carbunculus varies significantly between oceans and sexes and across latitudes in both oceans. Estimates of natural and fishing mortality were similar between oceans, but higher for females than males in both oceans. Evidence of greater fishing pressure on females than males is likely due to the larger size-at-age of females compared to males, assuming that selectivity of the fishing gear is related directly to fish size. Sex ratios were significantly female biased in both oceans despite this species being gonochoristic, and maturity schedules were similar between sexes in the Pacific Ocean. This species exhibits a protracted spawning season from mid-spring to autumn (i.e. October to May) in the Pacific Ocean. These results represent the first estimates of age-specific demographic parameters for E. carbunculus, and provide the foundation for the development of the first species-specific assessment models and harvest strategies for the species. Future stock assessment models for E. carbunculus should consider sex-specific demographic parameters and spatial variation in demography. Our results reveal substantial differences in biology between E. carbunculus and the ruby snapper E. sp., a cryptic congeneric species, and thus contribute to greater clarity in managing fisheries that are dependent on these two species. Furthermore, the improved information on the life history of E. carbunculus contributes to the broader sustainable management and improved food security for deepwater snapper fisheries in the Indo-Pacific region.